Pengaruh Kualitas Layanan Terhadap Loyalitas Melalui Kepuasan Tenant Di Mall Ciputra World Surabaya - Rizka Novianty Haninda (Fakultas Ekonomi Universitas Yos Soedarso, 2020)
The purpose of this study was to analyze the effect of service quality on tenant satisfaction and loyalty at Ciputra World Mall Surabaya; analyze the effect of satisfaction on tenant loyalty at Mall Ciputra World Surabaya; and analyze the effect of service quality on loyalty through tenant satisfaction at Ciputra World Surabaya Mall. This research uses a quantitative research approach. The population in this study were all tenants in Mall Ciputra World Surabaya as many as 453 people. While the samples used in this study were 82 tenants at Mall Ciputra World Surabaya. The analysis technique used in this study is Path Analysis. The results of the analysis that have been carried out can be concluded that the service quality variable directly affects the satisfaction and loyalty of tenants at Ciputra World Surabaya Mall with a positive direction; satisfaction variable influences tenant loyalty in Ciputra World Surabaya Mall directly in a positive direction, where the relationship is proven that satisfaction has a significant effect on tenant loyalty at Ciputra World Surabaya Mall with a significance value of less than 0.05; while service quality variables affect loyalty indirectly through tenant satisfaction at Ciputra World Surabaya Mall.Â Keywords: Service Quality; Customer Satisfaction; Customer Loyalty